267 AQualitative Exploration of Barriers and Recommendations from Women Leaders in Science and Agriculture. (22nd October 2022) - Owens, Casey M; Harlin, Julie F; Alvarado, Christine
Abstract: The purpose of the study was to conduct a qualitative exploration of barriers and recommendations from women leaders in science and agriculture. This study used a voluntary sample descriptive survey design that included 8 demographic, 11 importance/satisfaction, 7 negative/positive attribution, 11 barrier, and two open-ended questions. Responses were collected over a one-week period using social networking sites for women leaders in science and agriculture resulting in 60 respondents. The average respondents were all women in leadership roles in science and agriculture, 44years old, married, with no children, making between 60-120, 000 per year, who were also highly educated with a Masters or Doctoral degree and traveled more than two-three times per month. This study focused on responses of the two open-ended questions. Comments to the questions: "If there was one piece of advice you could go back and give yourself when you began your career, what would you share?" and "Please let us know if there was something else you wanted to share related to women in leadership roles in science and agriculture" resulted in 72 individual responses analyzed using the constant comparative method. Peer debriefings and inter-coder reliability were used to ensure trustworthiness and credibility. The qualitative analysis resulted in the following emerging themes: Having it all, Personal Development and Education, Personal Advocacy, and Networking. Though the results of this study are limited to this group of respondents, it is an important step in understanding the nuanced issues women face in leadership roles. One participant summed it up by stating: "The "take this opportunity now because it might never happen again" advice Iwas given for my career, Iused too much... and sometimes…the opportunities DO happen again... your life doesn't though, and at the end of the day, it's your family and health that stick."